Pengaruh Likuiditas dan Aktivitas terhadap Pertumbuhan Laba yang Dimediasi oleh Struktur Modal - Yohanes Yohanes; Cornelio Purwantini (Komunitas Dosen Indonesia, 2025)
The study aims to analyze the effect of liquidity and activity on profit growth as mediated by capital structure. The study population comprises of 92 companies operating in the food and beverage sector that are listed on the Indonesia Stock Exchange for the 2023 period. Data for this study were collected from secondary sources, specifically the official website of the Indonesia Stock Exchange (https://www.idx.co.id). The data were analyzed using the Partial Least Squares (PLS) structural equation modeling technique, supported by WarpPLS version 7.0 software. The results indicate that liquidity negatively affects profit growth, while activity and capital structure have no significant impact on profit growth. Furthermore, capital structure does not mediate the relationship between liquidity and profit growth, nor between activity and profit growth. These findings imply that optimal liquidity management is crucial for enhancing profit growth, and that efficient operational activities contribute positively to overall company performance.